Willingness of Indonesian Public on The Vaccination Programme as an Effort to Prevent Covid-19 - Herza Olivina (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The number of Covid-19 cases continues to increase, including in Indonesia. One of the efforts made by the Indonesian government to prevent a pandemic is to create and implement a Covid-19 vaccination program for the community. Therefore, the government is trying to urge the public to be willing to carry out a Covid-19 vaccine. This study was conducted to the willingness of the Indonesian public to the vaccination program as an effort to prevent Covid-19. The research method used is a qualitative approach by analyzing subjectively through the literature review method from PubMed, Clinical Key, Google Scholar, and Google Engine in Indonesian or English. The results showed that most Indonesians were willing to be vaccinated. However, there are also Indonesians who refuse to be vaccinated. The reason people refuse to be vaccinated against Covid-19 may be that they have different beliefs about the Covid-19 vaccine because of limited information about the type of vaccine, the availability of the vaccine, and the safety of the vaccine itself. the conclusion is that quite a lot of Indonesian people are willing to receive vaccinations but the government still needs to provide information, knowledge, and education about vaccination programs by involving all parties, both directly and the media so that Indonesian people who refuse or receive vaccines have the same perception or views as people who are willing received the Covid-19 vaccine.